Testosterone increases the virulence traits of uropathogenic Escherichia coli - Wu, Rongrong; Pettersson, Carolina; Demirel, Isak (Frontiers in Microbiology, 2024)
Uropathogenic E. coli (UPEC) is the most common cause of urinary tract infections (UTIs) in humans. Testosterone negatively impacts UTIs by affecting the immune response, leading to higher susceptibility of chronic cystitis in individuals with elevated testosterone levels, regardless of gender. Current research is mostly focused on how testosterone affects the host response to UPEC, but not so much is known about how testosterone directly affect UPEC virulence. The aim of the present study was to investigate the impact of testosterone exposure on the virulence of UPEC.We found that testosterone directly increases UPEC growth, endotoxin release and biofilm formation. We also found that testosterone-stimulated CFT073 increased colonization and invasion of bladder epithelial cells. Testosterone-stimulated CFT073 also increased the release of IL-1β and LDH from bladder epithelial cells. Additionally, by using a C. elegans survival assay we also showed that testosterone decreased the survival of CFT073 infected C. elegans worms. Taken together, our findings show that testosterone directly increases the virulence traits of UPEC.